All-electron MRCI+Q study on excited states of the SbBr molecule including spin-orbit coupling. (November 2020) - Zhou, Xiaohui; Yang, Ying; Zhang, Xiaomei; Liu, Yufang
Highlights: Total 34 Λ-S states of SbBr are accurately characterized at the MRCI+Q level. The SOC effect makes 34 Λ-S states split into 74 Ω states. Transition mechanisms of a 1 Δ-X 3 Σ − and b 1 Σ + -X 3 Σ − are illustrated. The SOC effect is indispensible for accurate spectroscopic determinations of SbBr. Abstract: In this work, we performed spin-orbit coupling (SOC) included MRCI+Q calculation on electronic states of SbBr. The SOC effect is treated by using the state interaction method in combination with the Breit-Pauli operator. Molecular orbitals are constructed with all-electron aug-cc-pwCVQZ-DK basis sets. Without SOC, total 34 Λ-S states of SbBr are obtained. It is found that the lowest three Λ-S states X 3 Σ −, a 1 Δ, and b 1 Σ + are characterized by a common electron configuration (π 2 ). All of them possess an especially deep potential well. Predissociations of a 1 Δ and b 1 Σ + are illuminated with the aid of SO matrix elements. Under the influence of SOC, total 74 Ω states arise from Λ-S states. The energy splitting of X 3 Σ − is calculated to be 868 cm −1, which well reproduces the measurement of 873 cm −1 . Particularly, SOC effects significantly improve the excitation energy ( Te ) of b 1 Σ + . The deviation is decreased from 1378 cm −1 to 233 cm −1 . In addition, the SOC effect has a great effect on transition properties of SbBr. This effect is responsible for the phosphorescence of transitions a 1 Δ-X 3 Σ − and b 1 Σ + -X 3 Σ −, and the corresponding transition mechanism is elucidated. Finally, radiative lifetimes of a 1 Δ and b 1 Σ + are determined at a millisecond level.